ANALISIS KELAYAKAN TEKNIS DAN FINANSIAL PRODUKSI JAGUNG BOSE INSTAN SEBAGAI INOVASI PANGAN LOKAL DI KABUPATEN TIMOR TENGAH SELATAN, NUSA TENGGARA TIMUR - Atikah, Husna; Susinggih Wijana; Widya Dwi Rukmi Putri; Nur Hidayat; Panji Deoranto (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
The rise of modern lifestyles has encouraged the development of various ready-to-eat products that are practical and value-added. Bose corn is a traditional food from East Nusa Tenggara (NTT) that has excellent potential to be instantized to overcome the constraints of long processing time. This study aims to analyze the technical and financial feasibility of instant Bose corn production as a local food innovation effort. The study was conducted in South Central Timor District using a case study approach with primary data through interviews and observations, and secondary data from related literature. The technical analysis showed that local raw materials are available with the potential for optimization through partnerships with farmers. The financial analysis showed a Net Present Value (NPV) of Rp 95,219,988 (>0), an Internal Rate of Return (IRR) of 13.94% (>12%), and a Payback Period of about 5 months, making it feasible to implement. In conclusion, the idea of instant Bose corn production is worth developing as an economically valuable and potential local food product innovation.